2020
DOI: 10.26656/fr.2017.4(s1).s12
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of selected local honey with Manuka honey based on their nutritional and antioxidant properties

Abstract: This study aimed to determine and compare the proximate composition, sugars content and antioxidant properties of selected Malaysian raw honey (Tualang, Gelam, Kelulut, Wild, and Pineapple) with Manuka honey. Proximate analysis (energy, carbohydrate, protein, fat, ash, moisture and total dietary fibre), sugar analysis (fructose, sucrose, glucose and maltose), total phenolic content (TPC) and antioxidant analysis (DPPH radical scavenging activity and linoleic acid oxidation assay) were conducted on the honey sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…Amongst the reviewed studies comparing the antioxidant properties of Tualang, Gelam and Kelulut honey, one study showed that Kelulut honey has the highest antioxidant properties in ranking after Manuka honey amongst Gelam and Tualang honeys [ 25 ]. By contrast, another study found Tualang honey to have higher antioxidant properties than Manuka, Kelulut, and Gelam honeys [ 27 ]. As mentioned earlier, the study also revealed higher free radical scavenging and antioxidant activity in Tualang honey than in Gelam and Borneo honeys [ 26 ].…”
Section: Physicochemical Characteristics Of Tualang Gelam and Kementioning
confidence: 98%
“…Amongst the reviewed studies comparing the antioxidant properties of Tualang, Gelam and Kelulut honey, one study showed that Kelulut honey has the highest antioxidant properties in ranking after Manuka honey amongst Gelam and Tualang honeys [ 25 ]. By contrast, another study found Tualang honey to have higher antioxidant properties than Manuka, Kelulut, and Gelam honeys [ 27 ]. As mentioned earlier, the study also revealed higher free radical scavenging and antioxidant activity in Tualang honey than in Gelam and Borneo honeys [ 26 ].…”
Section: Physicochemical Characteristics Of Tualang Gelam and Kementioning
confidence: 98%
“…53,54 The total phenolic content showed a proportional correlation with antioxidant activitiy. 23 The higher TPC of the MJ1 sample may be due to higher amount of total polyphenols in mango pulp as compared to passion fruit and pineapple. Previous study has reported TPC ranged from 129 mg GAE/g for pineapple to 546 mg GAE/g for mango in the methanol extractions.…”
Section: Color Propertiesmentioning
confidence: 98%
“…22 Besides, gelling agents, sweeteners, colouring, and flavourings are commonly used in the preparation of jelly to enhance the sensorial characteristics. 23 To increase consumer acceptance on jelly with excellent nutritional value without affecting taste and texture of the end product, tropical fruits that naturally contain antioxidants have recently been used as functional ingredients in jelly formulation. 24 This previous study has shown positive finding in bioactive compound and sensorial acceptance of product Therefore, in this study, antioxidant jelly was formulated using mango, passion fruit and pineapple juice as base ingredients and analysed for their nutritional composition, physicochemical, phytochemical, and sensory properties.…”
mentioning
confidence: 99%
“…Compared to Trigona Honey of South Sulawesi and Trigona of Malaysia which have different protein contents, Trigona of South Sulawesi contains 0.03% protein, 22 while Trigona of Malaysia contains 0.26% protein. 23 On the other hand, Apis honey contains 0.5% protein consisting of free amino acids and enzymes. 5 The percentage of protein contents may differ among different kinds of honey due to the sources of nectar consumed by the bees.…”
Section: Proteinsmentioning
confidence: 99%